2009
DOI: 10.1007/s12633-009-9032-0
|View full text |Cite
|
Sign up to set email alerts
|

Nostoc calcicola Immobilized in Silica-coated Calcium Alginate and Silica Gel for Applications in Heavy Metal Biosorption

Abstract: The present study reports the preparation and characterization of silica-based immobilization matrices for the purpose of metal accumulation using immobilized cyanobacterium Nostoc calcicola. Silica gel was prepared using aqueous sodium silicate and colloidal silica. Calcium alginate (CAG) beads were coated with silica using sodium silicate solutions. Microscopy observations and TTC tests confirmed that the immobilized cells were intact and viable. Ultrastructural studies with electron microscopy revealed a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…showed reduction activity of Cr(VI) in highly contaminated aqueous and soil environments [58]. Ramachandran et al [59] also studied the biosorption of heavy metals by encapsulation of the cyanobacteria Nostoc calcicola in two different matrices: silica dip-coated calcium alginate and silica gel from a silicate sol. In both cases the inorganic gels increased mechanical stability and adsorption capability of the cells, probably due to the interaction of the free silanol groups with the metals.…”
Section: Bioremediation Devicesmentioning
confidence: 99%
“…showed reduction activity of Cr(VI) in highly contaminated aqueous and soil environments [58]. Ramachandran et al [59] also studied the biosorption of heavy metals by encapsulation of the cyanobacteria Nostoc calcicola in two different matrices: silica dip-coated calcium alginate and silica gel from a silicate sol. In both cases the inorganic gels increased mechanical stability and adsorption capability of the cells, probably due to the interaction of the free silanol groups with the metals.…”
Section: Bioremediation Devicesmentioning
confidence: 99%
“…Burkholderia sp and Stereum hirsutum have been trapped in silica gels for chromium and malachite green removal, respectively [78,79]. Nostoc calcicola immobilized in silica-coated alginate beads were shown to have high metal accumulation properties, the silica coating enhancing the stability of the beads upon recycling [80]. Yeast cells were immobilized in zirconia for 4-chloro-2-methylphenoxyacetic acid degradation but the viability rate of encapsulated cells was very poor [81].…”
Section: Bio-hybrid Materials For Environment Monitoring and Remediationmentioning
confidence: 99%
“…Recently, hybrid materials consisting of algae-containing alginate beads trapped in a silica matrix were found suitable for the detection of the atrazine herbicide [100]. Such an approach is all the more interesting as previous works demonstrate both the possibility to tailor the silica gel optical properties to optimize algae survival [101] and the ability of the alginate network to be involved in the metal binding [80,102].…”
Section: Bio-hybrid Materials For Environment Monitoring and Remediationmentioning
confidence: 99%
“…38 Other examples of biopolymer-silica hybrid capsules have also been reported in the literature. 23,[39][40][41][42] However it has been found that silica is only deposited on the surface of the forming calcium alginate and not throughout the core of the bead, resulting in an insufficient porosity for the diffusion of nutrients and metabolites. In addition, cracking was still observed that resulted in cells leaching into the surrounding culture medium in which they can proliferate.…”
Section: Introductionmentioning
confidence: 99%